Sistem Informasi Verifikasi Dan Validasi Pendaftaran Ujian Komprehensif Berbasis Android (Studi Kasus Ilmu Komputer Di Universitas Bina Darma) - Randa Firnando; Novri Hadinata (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
An android-based comprehensive exam registration verification and validation information system. Registration for a comprehensive exam is a requirement that must be done by students to conduct a comprehensive trial. The problems of this research are (1) How to design a comprehensive online registration information system based on Android? (2) How to make a comprehensive online registration information system application. The objectives of this study are (1) to produce a comprehensive online registration information system design (2) to produce an android-based comprehensive registration information system application. A website-based comprehensive exam registration verification and validation information system to improve services in comprehensive registration. This system is built using the Model Prototype methodology, modeling Unified Modeling Language, Java programming language, Android Studio framework, and SMBD MySQL. This research resulted in the application of an Android-based comprehensive exam registration verification and validation information system that can be utilized by the Bina Darma University in the process of students who will carry out a comprehensive trial.